A practical approach to operative dentistry - Gray, Gordon B. (Gordon Brian); Daud Alaa H. (Hoboken, NJ : Wiley-Blackwell, 2021)
' Provides a synopsis of the theoretical knowledge followed by an illustrated step-by-step guide of clinical procedures within operative dentistry. Helps the reader develop and improve their manual dexterity -- one of the core areas of dental practice. Offers an overview of manipulation of dental materials used in teeth restoration. Highly illustrated with over 400 images showing step-by-step clinical procedures. Includes a companion website featuring step-by-step videos of clinical procedures and self-assessment questions'--
Instruments -- Isolation -- Dental Charting -- Minimal Invasive Dentistry -- Pit and Fissure Caries -- Posterior approximal restorations -- Restorations in Anterior Teeth -- Restorations of Lesions in Cervical Third -- Crowns and Inlays -- Porcelain fused to metal and all ceramic crowns
Includes bibliographical references and index.
Keywords: Dentistry, Operative -- methods; Oral Surgical Procedures; Tooth Diseases -- surgery; Dental Prosthesis; Dentistry, Operative